WANPRESTASI DALAM PERJANJIAN PINJAM MEMINJAM SECARA ANGSURAN ANTARA PEMINJAM DAN PEMBERI PINJAMAN DI KOTA PONTIANAK - NIM. A1011201012, SALSA BILLA PUTRI ANDINI (Fakultas Hukum Universitas Tanjungpura, 2024)
Abstract Lending and borrowing is not just goods but can be in the form of money so that an agreement arises between the two parties regarding the loan. There are cases of lending and borrowing in installments in the community in Pontianak City, Pontianak City District, namely between Lilik Purwanti (lender) and Yanti (borrower). Yanti (borrower) borrowed Rp. 100,000,000 (One Hundred Million Rupiah). Yanti also determined and gave Lilik Purwanti a profit of IDR 50,000,000 (Fifty Million Rupiah) so that when totaled it was IDR 150,000,000 (One Hundred and Fifty Million Rupiah). The payment deadline is 4 (four) years by paying monthly installments of IDR 3,125,000 (Three Million One Hundred Twenty Five Thousand Rupiah). Until finally the agreed deadline has expired, up to now in 2023, the installments have not been paid in full. So Yanti committed an act of default because he had neglected his performance or obligation to pay Lilik Purwanti (the lender) not on time. The problem formulation in this research is